The Family Lamiaceae of Manipur, India - Khomdram, S. D.; Nanda Devi, Y.; Singh, P. K. (Indian Forester, 2012)
The family Lamiaceae of Manipur which is represented by 110 species distributed under 39 genera is discussed. Among the genera reported, Clerodendrum is represented y maximum number of 14 species. Some species like Clerodendrum lasiocephalum C. B. Clarke, Orthosiphon wattii Prain and Premna milleflora C.B.Clarke are found endemic to North-East India. Updated record of Lamiaceae of the state is provided in the present paper.